2019
DOI: 10.3390/biom9090413
|View full text |Cite
|
Sign up to set email alerts
|

Serum Apurinic/Apyrimidinic Endodeoxyribonuclease 1 (APEX1) Level as a Potential Biomarker of Cholangiocarcinoma

Abstract: Diagnostic and/or prognostic biomarkers for cholangiocarcinoma (CCA) are still insufficient with poor prognosis of patients. To discover a new CCA biomarker, we constructed our secretome database of three CCA cell lines and one control cholangiocyte cell line using GeLC-MS/MS. We selected candidate proteins by five bioinformatics tools for secretome analysis. The inclusion criteria were as follows: having predicted signal peptide or being predicted as non-classically secreted protein; together with having no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Also, APEX1 was reported to be associated with some cancer types, including the cancers of colon, stomach, liver, kidney, and breast, as well as osteosarcoma[ 4 - 8 , 33 ]. Recent studies showed that APEX1 is an efficient biomarker for the diagnosis and prognosis of liver cancer[ 6 , 8 , 34 ]. However, the role of APEX2 in cancer is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Also, APEX1 was reported to be associated with some cancer types, including the cancers of colon, stomach, liver, kidney, and breast, as well as osteosarcoma[ 4 - 8 , 33 ]. Recent studies showed that APEX1 is an efficient biomarker for the diagnosis and prognosis of liver cancer[ 6 , 8 , 34 ]. However, the role of APEX2 in cancer is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Other diagnostic methods like ultrasonography, Computed tomography (CT) and magnetic resonance imaging (MRI) are more convenient than biopsy for liver disease [34]. A recent report shows that serum APEX1 can be used as a biomarker for cholangiocarcinomas [35]. It is plausible that serum APEX1 levels may be elevated in HCC patients and may be a more sensitive diagnostic biomarker.…”
Section: Agingmentioning
confidence: 99%
“…However, the clinical signi cance of APEX1 in cancer remains unclear, although APEX1 has been shown to be a positive regulator, contributing to the aggressive behavior of colon cancer behaviors [27]. Many studies have suggested increased APEX1 levels to be diagnostic and prognostic for cancer, and that APEX1 may be a therapeutic target for treatment of advanced cancer [28]. APEX1 expression has been inversely correlated with cellular senescence in human primary cells, while in cancer, low levels of APEX1 expression have been associated with increased senescence [29].…”
Section: Validation Of Apex1-regulated Gene Expression and Alternativmentioning
confidence: 99%